What Determines Preferences for an Electoral System? Evidence from a Binding Referendum - Guillem Riambau; Steven Stillman; Geua Boe-Gibson (Institute of Labor Economics (IZA), 2017)
Much has been written about politicians' preferences for electoral systems, yet little is known about the preferences of voters. In 1993, New Zealand had a binding electoral referendum on the same day as the general election where voters chose between keeping a single plurality system (First Past the Post) or introducing a pure proportional one (Mixed Member Proportional). This paper merges data from all nationwide polling stations to Census data on local voters to examine what drives citizens' preferences for an electoral system. We find that strategic partisan interest was a key driver; voters overwhelmingly preferred the system that most benefited their favorite party. However, socioeconomic characteristics and social values also mattered; people who held more progressive values, were outside the dominant religion and lived in urban areas were much more likely to vote to change to a proportional system. Survey data show that these findings hold at the individual level and further that individuals who were angry with the economy were much more likely to vote against the status quo, regardless of their background, party preferences or social values. This behavior is likely to have ultimately balanced the result in favor of Mixed Member Proportional.
Keywords: D72; D73; H11; 330; elections; electoral systems; voting behavior; referendum; New Zealand